Timor-Leste Public Expenditure and Financial Accountability Assessment 2018 : Public Financial Management Performance Report - World Bank (World Bank, Washington, DC, 2020)
Timor-Leste is making good progress in nation-building and its emerging governance systems have progressively developed into a largely disciplined PFM system. The main objective of this PEFA assessment is to establish a new baseline for Public Financial Management (PFM) performance measurement based on the 2016 PEFA framework. The assessment covers the Central Government of Timor-Leste, including all budget units under the Consolidated Fund of Timor-Leste. The assessment was conducted between June 2018 and July 2019 and the period of analysis was 2015, 2016 and 2017.